Grammar in Dictionaries of Languages for Special Purposes (LSP) - Mugdan, Joachim (HERMES - Journal of Language and Communication in Business, 1989)
In general monolingual and bilingual dictionaries and in the lexicographical literature on them, grammatical information is given a growing amount of attention. By constrast, grammar plays a rather minor role in LSP dictionaries although many users need a good deal of grammatical guidance in the production and reception of LSP texts.